Pelatihan Penganggaran, Panduan dan Program Pewara UNPAM bagi UMKM Jawara Guna Meningkatkan Kinerja UMKM di Bojongsari Depok - Nuryani, Anum; Rosyati, Tati; Fitriyana, Fina; Sofyan, Maulana; Harefa, Pasti Nugraha (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving the local economy, especially in developing areas like Bojongsari, Depok. However, one of the main challenges faced by MSMEs is the lack of proper financial management and budgeting skills. Many business owners struggle to allocate resources effectively, which often leads to inefficiencies and limits business growth. In response to this issue, a community service initiative was designed to enhance the budgeting capabilities of MSMEs under the Jawara (Jaringan Wirausaha) network. The goal of this initiative was to provide practical and interactive budgeting training for selected MSMEs, aiming to improve their understanding and skills in developing effective business budgets. Out of 244 registered MSMEs, 35 were selected to participate in this program. The stages of the program included problem and needs mapping, preparation of training modules, delivery of interactive training sessions, and integration with the PEWARA UNPAM program. The training was conducted from May 11–13, 2025, in Bojongsari Village, Depok. The methods used included participatory learning, distribution of practical financial management guides, and discussions to promote sustainable business practices. The outcome showed that participating MSME members gained a stronger awareness of the importance of sound budgeting. This was evident from their enthusiasm, engagement in discussions, and the variety of relevant questions posed during the sessions. The program successfully empowered entrepreneurs to manage their finances more effectively and sustainably.